Nonverbal Communication (NVC) and teacher presence in collaborative online learning - Bhatti, Dr. Muhammad Tariq; Teevno, Dr. Roshan Ali (The journal of contemporary issues in business and government, 2021)
Communication process requires a powerful combination of verbal and nonverbal process that is one of the abilities that every teacher needs to master. In communication, the estimation of sixty-five to seventy percent of the message is received by nonverbal and only thirty to thirty-five percent by verbal communication. This research seeks to analyze the effect of nonverbal communication by secondary teachers on the motivation and presence of students in a collaborative online learning environment. The information was gathered by questionnaires and interviews from both instructors and learners. The results showed that Nonverbal Communication can be an essential source of inspiration and attention for the learning process of students and a medium to attract their attention. Relying on the research outcomes that show the important role of Nonverbal Communication (NVC) in the teaching and learning process teachers by using the appropriate NVC types, eventually play a critical role during online collaborative teaching which can affect students’ motivation and higher collaborative learning participation. In order to accurately convey learning content to students, teachers will have to improve and expand positive interactions.